2010
DOI: 10.1162/jocn.2009.21246
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Right and Left Parietal Lobes in the Conceptual Processing of Numbers

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. sociated the conceptual processing of numbers with bilateral parietal regions (including intraparietal sulcus). However, the processes driving these effects remain unclear because both left and right posterior parietal regions are activated by many other conceptual, perceptual, attention, and response-selection processes. To dissociate parietal activation that is number-selective from parie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
68
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 56 publications
14
68
1
1
Order By: Relevance
“…The numerical decision task in the context of this study (odd or even) uses number semantics, which are represented in parietal cortex (Cappelletti et al, 2010). A previous study that investigated parietal cortex involvement in a range of different tasks that included converting orthography to phonology and a number task (although, in that instance, a simple subtraction) demonstrated parietal activity for both phonology and numbers (Simon et al, 2002).…”
Section: Discussionmentioning
confidence: 92%
“…The numerical decision task in the context of this study (odd or even) uses number semantics, which are represented in parietal cortex (Cappelletti et al, 2010). A previous study that investigated parietal cortex involvement in a range of different tasks that included converting orthography to phonology and a number task (although, in that instance, a simple subtraction) demonstrated parietal activity for both phonology and numbers (Simon et al, 2002).…”
Section: Discussionmentioning
confidence: 92%
“…First, patients with parietal lesions consistently show selective impairments in numerical skills (e.g., Dehaene and Cohen, 1997;Denes and Signorini, 2001;Grafman et al, 1982;Takayama et al, 1994;Warrington, 1982;Zorzi et al, 2002), whereas patients with lesions to other brain regions showed preservation of numerical skills (e.g., Butterworth et al, 2001;Cappelletti et al, 2001Cappelletti et al, , 2002Cappelletti et al, , 2005Crutch and Warrington, 2002;Diesfeldt, 1993;Jefferies et al, 2004Jefferies et al, , 2005Lemer et al, 2003;Zamarian et al, 2006). Second, functional MRI studies have systematically shown that numerical processing elicits greater activation in the parietal lobule than does nonnumerical processing (e.g., Ansari et al, 2006;Cappelletti et al, 2010;Eger et al, 2003;Knops et al, 2006;Le Clec'H et al, 2000;Piazza et al, 2004;Thioux et al, 2005;Zago et al, 2008; but see Göbel et al, 2004;Kadosh et al, 2008;Shuman and Kanwisher, 2004). Third, developmental dyscalculia has also been showed to be associated with structural abnormalities in the IPS regions (e.g., Isaacs et al, 2001;Kucian et al, 2006;Molko et al, 2003Molko et al, , 2004Rotzer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The present study required a baseline task that resulted in little or no activity in the reading-related pathways, which were known to include the posteroanterior extents of the left fusiform gyrus and superior temporal sulcus (Spitsyna et al, 2006). Visually presented numbers are like words and false font in that they consist of two-dimensional symbols with high contrast and spatial frequency, but processing of number-related semantics occurs in parietal cortex (Thioux et al, 2005;Cappelletti et al, 2010). Therefore, the study design was predicated on the assumption that explicit processing of visually presented numbers would result in low activity in the reading-related temporal lobe pathways, allowing the visualization of the extent of temporal lobe activity in response to both false font and words.…”
Section: Discussionmentioning
confidence: 99%
“…The other familiar symbols conveying visual information at high spatial frequencies are numbers, but number semantics are processed in parietal cortex (Thioux et al, 2005;Cappelletti et al, 2010). The localist model would predict that activity in ventral and lateral temporal neocortex would follow the profile words Ͼ false font ϭ numbers; in contrast, a profile of words Ͼ false font Ͼ numbers would be evidence against a localist model.…”
Section: Introductionmentioning
confidence: 99%